Análisis e interpretación financiera de los resultados obtenidos en los estados financieros del Comercial Katita del cantón Urdaneta periodo 2020 - Cedeño Aguilar, Jomayra Carolina (2021)
IAS 1 defines financial statements as accounting documents that constitute a structured representation of how the company is doing, whose objective is to ensure that they are comparable with financial statements of previous years or even with those of other companies, in order to determine the financial situation and financial performance of an entity. For this reason, the main objective of this case study is to know the financial and economic situation of the company, carrying out a vertical analysis and applying relevant financial indicators that allow the owner of the commercial to provide suggestions aimed at solving shortcomings. Among the most relevant results obtained, it was determined that its financial structure is represented in its greatest proportion by non-current assets that are equivalent to 85.29%, while in its economic structure the most significant item is income with 100% of your sales, In addition, it was demonstrated that its credit policy is not recovering within the term established by the company and even the commercial one is not taking advantage of its resources for financing.